(untitled) (Third Sector Social Economic Review, 2025)
In today’s market conditions characterised by technological developments, the most important element of sustainable competition of organisations is innovation. In this context, it is important for businesses to identify the factors that increase organisational innovation at individual and organisational level and to make strategic plans for the development of these factors. Within the scope of the research, the role of digital leadership, digital organisational culture and individual skills within the organisation as determinants of organisational innovation is discussed. In this direction, it is aimed to determine the role of digital organisational culture in the effect of digital leadership on organisational innovation through the use of organisational skills. The study included 382 civil aviation ground handling employees. The data were analysed using SPSS 26.00 and Smart PLS 4.1. According to the findings of the study, digital leadership increases the use of individual skills within the organisation and organisational innovation, while the use of individual skills within the organisation increases organisational innovation. In addition, the mediating role of the use of individual skills within the organisation in the effect of digital leadership on organisational innovation was determined. The analysis of the moderating role of digital organisational culture revealed that digital organisational culture has a moderating role in the effect of digital leadership on organisational innovation through the use of organisational skills and that digital organisational culture strengthens these effects. Organisations can ensure that digital leadership transforms into sustainable organisational innovation by promoting a culture that values and uses individual skills.